## Answer :

First we free one value...

-y=4-3x

y=-4+3x

now we use this solve for x

6x+3(-4+3x)=136x-12+9x=13

15x= 13+12

x= 25/15

Now that we have x we find y

y= -4+3(25/15)y=1

Now we check

6(25/15)+3(1)=1310+3= 13

13=13

3x-y=4

3(25/15)-1=4

5-1=4

4=4

yeah... so x= 25/15 and y= 1

now elimination (Yay... *note of sarcasm*)

6x+3y=133x-y=4

we need to sum and both equation in a way to eliminate one variable... so we multiply 3 to eliminate y so...

6x+3y=133x-y=4 (*3)

6x+3y=139x-3y=12

now we resolve

15x= 25

x= 15/25

now we could use x in any equation to find y

6(25/15)+3y=1310+3y=13

3y=13-10

y=3/3

y=1

3x-y=4

3(25/15) -y= 4

5-y= 4

-y=4-5

-y=-1

y=1

So now we check if it is correct

6(25/15)+3(1)=1310+3= 13

13=13

3x-y=4

3(25/15)-1=4

5-1=4

4=4

So yeah... we can now tell that x= 25/15 and y = 1

your answer is y= 1...

Hope it helped...